Globalizing Chinese Culture, Localizing Buddhist Teachings: the Internationalization of Foguangshan - Chandler, Stuart (Journal of global buddhism, 2002)
Foguangshan, one of the most prominent Buddhist organizations in Taiwan, has over the past decade also developed a significant network of temples around the globe. With more than 150 centers dispersed on five continents and serving millions of devotees, the Foguang "empire," as Washington Post journalist Kevin Sullivan has dubbed the phenomenon, is now arguably one of the most extensive and best organized Buddhist groups in the world (Sullivan 1996, A22). There are certainly few monks who can claim to have gathered as large a sangha as has Foguangshan's founder, Master Xingyun, who currently supervises more than thirteen hundred disciples. In this essay, I describe the various factors that have contributed to Foguangshan's remarkable success in transforming itself from a local institution into one of truly international magnitude. After placing Foguangshan's expansion in historical perspective, I analyze its demographics and the methods that the master and his disciples have relied upon to carry out their ambitious objectives. Through this discussion, the challenges and tensions inherent within the group's mission come to light. The essay concludes by disclosing Master Xingyun's positive appraisal of the religious implications of globalization. This Foguang material provides one piece of evidence that in the post-modern The Journal of Global Buddhism 46world people's primary referent for communal identity may very well increasingly revert from national to religious symbols and myths.